EVALUATION OF AN INTERRELATION OF TARGET BLOOD PRESSURE ACHIEVEMENT AND COMPLICATIONS AND OUTCOMES OF PREGNANCY IN ARTERIAL HYPERTENSION - V. S. Chulkov; N. K. Vereina; S. P. Sinitsyn; V. F. Dolgushina (Кардиоваскулярная терапия и профилактика, 2014)
Aim. To evaluate the influence of target BP achievement on clinical course and outcomes of pregnancy in pregnant women with arterial hypertension (AH).Material and methods. A cohort study with prospective cohort. Totally 300 pregnant women included; of those in to the 1st group 103 included with AH, who had not reached target BP; into the 2nd – 97 women with AH, who had reached target BP; control consisted of 100 women without AH. Women underwent clinical examination and observation, analysis of medical data, standard laboratory and instrumental investigation, genetic investigation by polymerase chain reaction.Results. Women who had not reached target BP pregnancy complicated more often with fetus development retardation and pre-eclampsy, and in pregancy outcomes there were preterm delivery and antenatal fetus death, newborns from this group had lower weight and height; also they had more often mutation of D-allele of ACE gene (I/D) and mutant C-allele of receptor 1 type angiotensine II gene (ATR11166 A/C) comparing to the group with achieved BP and with controls. By the result of logistic regression study the factor independently associated with total worse outcome, were premature deliveries in anamnesis - increase the risk almost 6 times (OR=5,93, 95% CI 1,83-19,2; p=0,003), pre-eclampsy during current preganancy – increases risk 3,7 times (OR=3,68, 95% CI 1,48-9,16; p=0,005), and target BP acievement (less than 140/90 mmHg) decreases the risk of total negative outcome 8 times (OR=0,12, 95% CI 0,05-0,28; p<0,001).Conclusion. Target BP achievement in pregnant women with AH might be an independent factor influencing the prevalence of obstetric complications and negative outcomes of pregnancy. A definite impact on target BP levels achievement make genetic polymorphisms of renin-angiotensin system genes.